A wood-derived hierarchically porous monolithic carbon matrix embedded with Co nanoparticles as an advanced electrocatalyst for water splitting. Issue 10 (12th August 2019) - Li, Yanan; Min, Shixiong; Wang, Fang
Abstract : A wood-derived hierarchically porous monolithic carbon (N-HPMC) matrix embedded with Co nanoparticles (Co@N-HPMC) is developed as an efficient electrocatalyst for water splitting. Abstract : The rational design and development of advanced electrocatalysts for water splitting based on porous monolithic carbon as a host matrix of earth-abundant transition metals (TMs) is highly desirable and actively pursued owing to their promising practical applications, but remains a grand challenge. Herein, a wood-derived N-doped hierarchically porous monolithic carbon (N-HPMC) matrix embedded with Co nanoparticles (Co@N-HPMC) is fabricated by direct two-step carbonization of natural wood (NW) loaded with Co/CoO x . The monolithic N-HPMC matrix has numerous aligned and open microchannels, abundant porosity, and high conductivity, which afford rapid electron transfer and mass transport, while the embedded Co nanoparticles (Co NPs) have high dispersion and a strong synergistic interaction with the N-HPMC matrix, which offer an abundance of highly active sites. As a result, the monolithic Co@N-HPMC electrode exhibits excellent electrocatalytic water splitting performance in 1.0 M KOH, and it requires overpotentials of 128 and 297 mV to reach a current density of 10 mA cm −2 for the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), respectively. More notably, an alkaline electrolyzer for overall water splitting (OWS) assembled by employing Co@N-HPMC as both the cathode and anode achieves current densities of 10 and 50 mA cm −2 at cell voltages of 1.77 and 2.16 V, respectively. This study provides an effective strategy to fabricate noble-metal-free high-performance monolithic electrocatalysts for commercial applications.